Better journalism or better profits?: A key convergence issue in an age of concentrated ownership - Stephen Quinn (Asia Pacific Network, 2004)
Convergence has become an accepted form of journalism at media organisations around the world. These organisations are adopting a range of business models to find ways to pay for these innovations. The main drivers behind this radical change in media production are the disruptive forces that these two drivers behind this radical change in media production are consumers' changing media habits, cheaper digital technology, and the disruptive forces that hese two drivers generate. Technology also maes possible new forms of storytelling, which potentially allows jounrlaists the chance to do better jounrlists through convergence. This article focuses on the key issue of whether editorial managers and journalists are embracing convergence to save money, or to do better journalism. It begins by defining convergence (while accepting the wide variety of definitions) and describing two main models of implementation. It then considers the factors that hinder its introduction. Examples are provided of converged media around the world. This article ends with a warning about the dangers for democracy of misapplied convergence in an era of increasing concentration of ownership.